Sustaining Informatics Education by Contests - Dagienė, Valentina (Teaching Fundamental Concepts of Informatics, 2010)
Three decades ago high school computing was highly consistent with academic and professional world. This consistency was destroyed when school curricula began to emphasize information and communication technology skills at the expense of computer science. Recently many countries began to think how to re-establish informatics education in schools and how to attract pupils to choose optional modules related to computer science. Although informatics is not taught as a discipline in many countries, pupils are invited to participate in different contests on informatics organized all over the world. When pupils get interested in programming contests, they are looking for training and gain some informatics education. Contests are exceptionally valuable for motivating and involving pupils in computer science. The current paper discusses the contests and olympiads in informatics arranged internationally and continuously. The main attention is paid to the model of International Olympiad in Informatics and International Contest on Informatics and Computer Fluency (named Bebras in Lithuanian, or Beaver in English).